2007
DOI: 10.1002/ejoc.200700101
|View full text |Cite
|
Sign up to set email alerts
|

Uronic Acids in Oligosaccharide Synthesis

Abstract: This Microreview covers some general strategies for the preparation of uronic acid residues and their incorporation into anionically charged oligosaccharides. Two distinct strategies can be recognized: (1) glycosylation followed by oxidation, and (2) oxidation of the monosaccharide building

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 149 publications
(77 reference statements)
2
38
0
Order By: Relevance
“…The modest yield was attributed to the presence of the protected aminopentyl linker, which in our experience lowers yields of glycosylations. Furthermore, uronic acids are notoriously poor glycosyl acceptors, 25 which is attenuated by the electron-withdrawing groups at C-2 and C-6 of acceptor 11 . The process of Fmoc removal and glycosylation was repeated twice by employing glycosyl donors 8 and 9 to give fully protected octasaccharide 16 .…”
Section: Resultsmentioning
confidence: 99%
“…The modest yield was attributed to the presence of the protected aminopentyl linker, which in our experience lowers yields of glycosylations. Furthermore, uronic acids are notoriously poor glycosyl acceptors, 25 which is attenuated by the electron-withdrawing groups at C-2 and C-6 of acceptor 11 . The process of Fmoc removal and glycosylation was repeated twice by employing glycosyl donors 8 and 9 to give fully protected octasaccharide 16 .…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the presence of the electron withdrawing carboxylic acid, glucuronic acid thioglycoside derivatives have been rarely used as glycosyl donors 2831. Instead, thioglucosides are typically employed, which require oxidation state adjustment after the glycosylation 28,32. It will be desirable to be able to use protected glucuronic acid derivatives directly as glycosyl donors.…”
Section: Resultsmentioning
confidence: 99%
“…[39][40][41][42][43][44][45] Further, aldehydes generated by partial oxidation of polysaccharides can undergo Schiff-base formation with primary amines [43,46] (e.g., lysine residues) for the covalent attachment of proteins. [47,48] In initial studies, we identified conditions to electrodeposit and activate chitosan films for protein assembly.…”
mentioning
confidence: 99%